2002
DOI: 10.1186/bcr567
|View full text |Cite
|
Sign up to set email alerts
|

Waist–hip ratio and breast cancer risk in urbanized Nigerian women

Abstract: BMI = body mass index; LRT = likelihood ratio test; SHBG = sex hormone binding globulin; WHR = waist-hip ratio. (Print ISSN 1465-5411; Online ISSN 1465-542X). This is an Open Access article: verbatim copying and redistribution of this article are permitted in all media for any non-commercial purpose, provided this notice is preserved along with the article's original URL. Breast Cancer Research Vol 5 No 2 Adebamowo et al. Research article Waist-hip ratio and breast cancer risk in urbanized Nigerian women Abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…These study findings confirmed our pilot data and another study in Nigerian population that WHR was associated with both pre- and post-menopausal breast cancer, although the two previous studies did not control for overall obesity [29,36]. A study conducted in North Carolina found that the positive association between WHR and breast cancer existed in African Americans [37], whereas a recent report from California showed no association between WHR and breast cancer in African Americans [38].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These study findings confirmed our pilot data and another study in Nigerian population that WHR was associated with both pre- and post-menopausal breast cancer, although the two previous studies did not control for overall obesity [29,36]. A study conducted in North Carolina found that the positive association between WHR and breast cancer existed in African Americans [37], whereas a recent report from California showed no association between WHR and breast cancer in African Americans [38].…”
Section: Discussionsupporting
confidence: 90%
“…Data from other populations are not always consistent either, but two summaries might be made from review of the literature and this study. First, most studies showed that waist circumference or WHR was either positively associated with increased risk of breast cancer or there was no association [715,1721,29,36,37]. while few studies found inverse association [22,39], suggesting that central obesity is more likely to be a risk factor and chance variability may be a reason for null association, especially when sample size is small.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 9163 retrieved references, 2680 references were excluded because of duplication, 6273 references did not relate to the objective of this review, and 160 references did not meet the eligibility criteria. Eventually, we included 50 studies in the meta-analysis including 15 cohort studies [4][6], [10], [15], [23][32] involving 2,104,203 people and 3,414,806 person-years and 35 case-control studies [8], [9], [33][65] involving 71,216 people. Some case-control and cohort studies evaluated breast cancer during premenopausal period, some during postmenopausal period and some during both periods.…”
Section: Resultsmentioning
confidence: 99%